Landless Workers’ Movement and its contributions to food security during the COVID-19 pandemic in Brazil - Laurentino, Jackson Silva Lima; Silva, Adarlam Tadeu da; Silva, Erica Rodrigues da; Silva, Catarine Santos da; Almeida, Luymara Pereira Bezerra de (Saúde e Sociedade, 2022)
The COVID-19 pandemic worsened hunger and food insecurity around the world, leading to mobilization of social movements to alleviate this scenario. This documentary study characterizes and analyzes the Landless Workers’ Movement’s actions and contributions to promote food security during the COVID-19 pandemic in Brazil. Data was collected through online search tools. The documents found were verified for their veracity and analyzed using Bardin’s content analysis. Of the documents found, most were news. Donations and sale of food from the movement’s organic and agroecological production, and seed donations for planting were the actions carried out. These actions took place in different regions of the country and sought to improve food access and availability to vulnerable populations, thus promoting access to quality and safe food. This demonstrates that the actions carried out by the movement contributed to combating hunger during the pandemic, highlighting the importance of rural movements in promoting food security.